Developing heuristic algorithms for optimisation of location-allocation of fuel-distribution network. (2018) - Bagherinejad, Jafar; Mirzaei, Maryam
The aim of this paper is to determine the optimal locations for the construction of refuelling stations for vehicles in urban distribution networks including paths and intersections. The objective is to maximise the covered demands with certain number of facilities. For this purpose, mathematical modelling of location-allocation based on the maximal coverage is developed. Considering the service capacity constraint for refuelling stations is one of the innovations of this research. Changing the approach from the node-based to path-based for demands and facility location makes a new way to the location problems of this field. The proposed algorithms have been approved by solving a numerical example. The overall findings show that in the maximal covering of demands, the third heuristic algorithm is better than others based on the fewer number of determined stations.